DIDACTIC TERMS OF USE OF BIOGRAPH INFINITI SPECIALIZED SOFTWARE IN UKRAINE’S HIGHER EDUCATION INSTITUTIONS - Olha M. Lunhol; Olha A. Haborets; Hanna M. Kolieva; Artur O. Voloboiev (Інформаційні технології і засоби навчання)
The article shows the possibility of using hardware ProComp Infiniti System with BioGraph Infiniti Software in the educational process of higher education institutions in Ukraine in different directions of training, including specific training conditions. The Infiniti system monitors and records a wide range of physiological and mechanical signals, analyzes and provides real-time biofeedback through various auditory and visual aids. The authors analyzed scientific and professional literature on the development and introduction of specialized software products in the educational process of higher education institutions in Ukraine and across the globe. The paper defines the advantages and prospects of carrying out a cycle laboratory work and research with BioGraph Infiniti tools and the principles of work with ProComp Infinity hardware. The didactic conditions of use of BioGraph Infiniti Software in the educational process of higher medical education institutions and universities of internal affairs of Ukraine are defined for formation of informational and subject competence of Ukraine’s students. Attention is focused on ensuring the flexibility of the educational process by means of variability, changes in the content and methods of education, forms of organization of educational classes with a direct practical component, a combination of different education methods for students of various types of higher education institutions. The possibilities of development of a series of laboratory works with their further placement in the virtual educational environment "Laboratory works system with specialized software Biograph Infiniti" are considered. Each laboratory work is created according to the principles of scientificity, integrity and professional orientation of education and includes 3 levels: general (basic), psychological and medical-biological.